2021
DOI: 10.1093/pm/pnab014
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Genicular Nerve Blockade With Corticosteroids Using Either Classical Anatomical Targets vs Revised Targets for Pain and Function in Knee Osteoarthritis: A Double-Blind, Randomized Controlled Trial

Abstract: Objective Compare the effectiveness of genicular nerve blockade (GNB) using classical anatomical targets (CT) versus revised targets (RT) in patients suffering from chronic knee osteoarthritis pain. Design Double-blinded randomized controlled trial. Setting Pain medicine center of a teaching hospital. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 26 publications
0
19
0
Order By: Relevance
“…Recently, there has been increasing interest in targeting up to 10 additional nerves to improve the efficacy of the procedure. Moreover, several studies have shown that targeting more branches improves the treatment efficacy compared to the three nerve techniques [ 17 , 26 28 ]. However, expanding the number of targeted nerves may increase side effects, including motor injury, so safety concerns should always be considered.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, there has been increasing interest in targeting up to 10 additional nerves to improve the efficacy of the procedure. Moreover, several studies have shown that targeting more branches improves the treatment efficacy compared to the three nerve techniques [ 17 , 26 28 ]. However, expanding the number of targeted nerves may increase side effects, including motor injury, so safety concerns should always be considered.…”
Section: Discussionmentioning
confidence: 99%
“…1 ). Depending on physician preference and based on recent anatomical updates, additional nerves including the recurrent fibular nerve (RFN) and the infrapatellar branch of the saphenous nerve (IPBSN) were blocked [ 15 , 17 , 19 ]. The anatomic locations for the additional genicular nerves were identified as follows ( Fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Guler et al (23) showed that ultrasound-guided genicular nerve blockade with a total mixture of 5 ml of 2% lidocaine and 40 mg of triamcinolone, to patients with knee osteoarthritis has sustained improvement in pain, physical function, and physical capacity for up to 12 weeks. Fonkoue et al (24) performed a single session genicular nerve blockade with a mixture of lidocaine and triamcinolone, using scopy-controlled classic and revised target techniques, to patients with chronic knee pain due to osteoarthritis. In both groups, improvement was detected at the 12 th -week control compared to baseline in pain severity assessed by NRS, functionality assessed by WOMAC, and physical and mental health assessed by SF-12 (24).…”
Section: Discussionmentioning
confidence: 99%
“…Fonkoue et al (24) performed a single session genicular nerve blockade with a mixture of lidocaine and triamcinolone, using scopy-controlled classic and revised target techniques, to patients with chronic knee pain due to osteoarthritis. In both groups, improvement was detected at the 12 th -week control compared to baseline in pain severity assessed by NRS, functionality assessed by WOMAC, and physical and mental health assessed by SF-12 (24). The common point of these studies in patients with knee osteoarthritis is that long-term efficacy was demonstrated with a single-session block with added steroids.…”
Section: Discussionmentioning
confidence: 99%